FAKTOR-FAKTOR YANG MEMENGARUHI PERMINTAAN BUAH NAGA (HYLOCEREUS COSTARICENSIS) DI KOTA PALU - Hikmah, Dian Nurul; Effendy, Effendy; Rauf, Rustam Abdul (AGROTEKBIS, 2017)
Dragon fruit (Hylocereus costaricensis) is not the originally Indonesia fruit because this fruit is from Middle America and North America, however it can grow well in Indonesia because Indonesia climate is suitable for the its development and growth. Dragon fruit in Central Sulawesi just be developed on 2012. At the beginning, only saveral farmers interest to cultivate, as the time running, price and the demand of dragon fruit getting high cause the farmers interest to develop it. This study aims to determine the effect of income factors, prices, the number of dependents of the familly, age and sex on the demand of dragon fruit in Palu City. This research was conducted at Swalayan BNS in Palu City from March to April 2017. The analysis tool used in this research is multiple linear regression. The results of this study showed that there are several influence of factors effecting the demand which consist of income, the price of dragon fruit, the number of family dependents, age and sex on the demand of dragon fruit in Palu City. It can be concluded that the income variable, dragon fruit price, and age have significantly influenced on the demand for dragon fruit in Palu city, while the number of family dependents and sex was not significantly affect the demand for dragon fruit in Palu City.Â Keywords: Dragon fruit, demand, Multiple linear regression analysis.